The Role of Artificial Intelligence in Midwifery: A Scoping Review of Benefits, Challenges, and Ethical Implications - Cyril B. Romero; Ramil Edward V. Cariño; Charmae B. Ignacio (Buletin Ilmu Kebidanan dan Keperawatan, 2025)
Artificial Intelligence (AI) is rapidly transforming healthcare and holds significant potential to improve maternal and neonatal outcomes through its application in midwifery. This scoping review investigates the role of AI in midwifery, emphasizing its benefits, challenges, and ethical implications. Guided by the Arksey and O’Malley framework, a systematic literature search was conducted using Google Scholar (2014–2024) via the Publish or Perish software, with keywords including "Artificial Intelligence in Midwifery," "AI and Maternal Health," and "Machine Learning in Obstetrics." A total of 15 articles were reviewed. The findings reveal five key areas where AI contributes to midwifery practice: (1) early detection of pregnancy complications such as preeclampsia and gestational diabetes using predictive machine learning models; (2) remote monitoring of pregnancy through wearable devices and mobile applications; (3) use of virtual assistants and chatbots for patient education and psychological support; (4) optimization of healthcare facility management, including electronic health records and resource allocation; and (5) AI-based training simulations for midwives to enhance clinical competencies. While these advancements offer promising improvements, challenges remain, including high implementation costs, limited infrastructure, and data privacy concerns. Ethical considerations stress the importance of ensuring AI complements—rather than replaces—the empathetic, human-centered care that is central to midwifery. This review highlights the transformative potential of AI in midwifery and advocates for its ethical and balanced integration to maximize benefits for maternal and neonatal health.